Implementasi Manajemen Berbasis Sekolah pada Satuan Pendidikan - Anis Zohriah; dedi abu syamsudin; Rijal Firdaos (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This paper aims to find the urgency of implementing School-Based Management in education units, using a qualitative approach through the library study method, namely reviewing several articles, books and other documentation related to the concept of implementing school-based management, so as to find a new theory of strategy and the impact it provides. in education units in improving the quality of education through the implementation of SBM. School-based management (SBM) is an educational model that gives autonomy or authority to schools to be able to manage their own affairs with their respective environmental conditions. Implementation of school-based management can improve the quality of education by implementing the right strategy. There are at least 3 (three) stages that can be carried out including the socialization stage, the piloting stage, and the dissemination stage. In addition to utilizing this strategy, the role of the school principal as a leader is also urgently needed to coordinate all components of the school so that they can carry out school-based management properly in order to achieve an increase in the quality of education. Keywords: Implementation, Management, School